First‐in‐Human Phase I Study of MBC‐11, a Novel Bone‐Targeted Cytarabine‐Etidronate Conjugate in Patients with Cancer‐Induced Bone Disease. (9th November 2018) - Zinnen, Shawn Patrick; Karpeisky, Alexander; Von Hoff, Daniel D.; Plekhova, Larisa; Alexandrov, Alexander
Abstract: Lessons Learned: Results are consistent with MBC‐11 targeting and treating cancer‐induced bone lesions by concentrating cytarabine and etidronate at the site of disease. MBC‐11 was well tolerated, with an maximum tolerated dose of 5 mg/kg per day and myelosuppression as the principal toxicity. Treatment significantly reduced cancer cell activity in over half of bone lesions detected at baseline. MBC‐11 pharmacokinetic and pharmacodynamic parameters are consistent with the novel drug design goals, and encouraging results warrant further clinical development. Background: MBC‐11 is a first‐in‐class conjugate of the bone‐targeting bisphosphonate etidronate covalently linked to the antimetabolite cytarabine (araC). This first‐in‐human phase I dose escalation study assessed safety, tolerability, maximum tolerated dose (MTD), plasma pharmacokinetics, bone turnover, tumor biomarkers, and bone lesion activity by fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F‐FDG‐PET/CT) imaging. Methods: Fifteen patients with advanced solid cancers and cancer‐induced bone disease (CIBD) were treated with 0.5–10 mg/kg per day of MBC‐11 administered daily for 5 days of every 4 weeks for up to four cycles. Results: Grade 1–2 myelosuppression, involving all lineages, was the principal toxicity. Two of three patients treated with 10 mg/kg experienced dose‐limiting grade 4 neutropenia and thrombocytopenia (adverse event [AE] duration ≤5 days); the MTD was 5 mg/kg. Four of five patients with pretreatment elevations of the bone resorption marker TRAP5b (tartrate resistant acid phosphatase‐5b) had persistent decrements. Six of 13 patients who reported baseline pain noted a reduction after MBC‐11. 18 F‐FDG‐PET/CT imaging demonstrated partial metabolic responses in three patients and stable metabolic responses in three other patients. SUVmax (standard unit of emission normalized to total uptake) was reduced by at least 25% in 110 (52%) of 211 bone lesions. Significant activity was noted across all doses, and myelosuppression increased with dose. Conclusion: At MBC‐11 doses that were well tolerated, substantial reductions in metabolic activity of bone‐associated cancer cells provide a foundation for further disease‐directed efficacy studies.